1995
DOI: 10.1007/bf01298903
|View full text |Cite
|
Sign up to set email alerts
|

Few-neutron removal from238U at relativistic energies

Abstract: Abstract. As part of a comprehensive study of uranium fragmentation at relativistic energies at the GSI projectile fragment separator, FRS, inclusive neutron-removal cross sections have been measured for several zr~ channels at projectile energies of 600 and 950 A MeV using targets of A1, Cu and Pb. The variation of the experimental cross sections with target nuclear charge is used to disentangle nuclear and electromagnetic contributions. The electromagnetic cross sections agree surprisingly well with a simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 31 publications
(56 reference statements)
1
10
0
Order By: Relevance
“…Therefore, our data give evidence for the excitation of the double giantdipole resonance in uranium. This result is in good agreement with recently reported neutron removal cross sections of 238U [14]. In that publication it was shown that the cross sections for ln-4n removal are well reproduced by similar WW calculations which use the same parametrization of the fission probability.…”
Section: O-tota I ----~R E M F "4-~tn Uclea Vsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, our data give evidence for the excitation of the double giantdipole resonance in uranium. This result is in good agreement with recently reported neutron removal cross sections of 238U [14]. In that publication it was shown that the cross sections for ln-4n removal are well reproduced by similar WW calculations which use the same parametrization of the fission probability.…”
Section: O-tota I ----~R E M F "4-~tn Uclea Vsupporting
confidence: 89%
“…While the 1-phonon excitations were well reproduced by the calculations, the cross sections of the 2-phonon excitations were underpredicted [12,13]. In a recent experiment in to 4n removal cross sections of 23SU-projectiles impinging on A1, Cu and Pb targets were measured [14]. The results were well reproduced by WW-calculations including the excitation of the double GDR.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…As argument for this new point of view, let us recall that another decay mode of the DGDR has already been discovered; it is the 3n-decay of the DGDR, recently observed in hevy-ion reactions at relativistic energies [13].…”
Section: -The A-decay Of the Dgdr Of A Fissioning Nucleusmentioning
confidence: 98%
“…Experimentally, measurements have investigated various decay branches, like γ-rays, neutron emission, and fission, see, e.g., Refs. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Almost exclusively, all the experimental data have been compared with calculations using the semi-classical Weizsäcker-Williams method of virtual photons [21][22][23][24] which has been shown to give an appropriate description of the process [24].…”
mentioning
confidence: 99%